2019
DOI: 10.1007/s00167-019-05614-z
|View full text |Cite
|
Sign up to set email alerts
|

Early knee osteoarthritis prevalence is highest among middle-aged adult females with obesity based on new set of diagnostic criteria from a large sample cohort study in the Japanese general population

Abstract: Purpose A few new criteria for early detection and prevention of early knee osteoarthritis (EKOA) have been proposed. However, its prevalence, risk factors, relationship with function and prognosis have not been clarified. The purpose of this study was to investigate the prevalence of EKOA and its risk factors in the Japanese general population. Methods A total of 1104 volunteers (443 males, 661 females) who participated in the Iwaki cohort study in Japan were enrolled in this cross-sectional study. Their bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 53 publications
3
42
0
3
Order By: Relevance
“…Whilst EKOA is solely diagnosed based on mild knee pain and disabilities, it can be clearly distinguished from both normal and symptomatically abnormal knees. In their cohort study, Sasaki et al reported that the highest prevalence of EKOA was www.nature.com/scientificreports/ observed in females aged ≥ 50 years, who had reduced knee function and QOL; the risk factors for EKOA were age, female sex, obesity, and previous knee injury, similar to those of definitive knee OA 6 . The association of serum biomarkers and EKOA has not been well established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst EKOA is solely diagnosed based on mild knee pain and disabilities, it can be clearly distinguished from both normal and symptomatically abnormal knees. In their cohort study, Sasaki et al reported that the highest prevalence of EKOA was www.nature.com/scientificreports/ observed in females aged ≥ 50 years, who had reduced knee function and QOL; the risk factors for EKOA were age, female sex, obesity, and previous knee injury, similar to those of definitive knee OA 6 . The association of serum biomarkers and EKOA has not been well established.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of changes to the knee at an early phase of OA may help prevent the progression to definitive OA. Although many studies had reported the features of early phase of knee OA 1,6,17,18 , there was no clear definition for early phase of knee OA; however, Luyten et al defined the new criteria 5 . Whilst EKOA is solely diagnosed based on mild knee pain and disabilities, it can be clearly distinguished from both normal and symptomatically abnormal knees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knee osteoarthritis (KOA) is a major public health problem in the middle-aged to elderly population and negatively affects patients' activities of daily living (ADL) and quality of life (QOL) [1][2][3] . Early diagnosis and treatment of KOA are required to reduce its health care burden 4 , by preventing disease development and progression [5][6][7][8] . The concept of early KOA is characterized by the presence of knee symptoms in the absence of de nitive radiographic abnormalities (Kellgren-Lawrence [KL] grade 0-1).…”
Section: Introductionmentioning
confidence: 99%
“…Disadvantages of progressed KOA include high treatment costs, decreased productivity, and absence from work 3 ; therefore, early diagnosis is crucial for early treatment and preventative interventions 4 . A recent epidemiological study revealed that the highest prevalence of early KOA (EKOA) was observed in females aged ≥ 50 years, owing to factors such as age, female sex, obesity, and previous knee injury 5 . The major causal factor of EKOA and de nitive KOA (DKOA) was sex 6,7 .…”
Section: Introductionmentioning
confidence: 99%